The Role of the Academic Library in Capturing Indigenous/Local Knowledge and how such a Programme can be Formalised: Examples from Ghana, Tanzania Uganda and South Africa - Nyantakyi-Baah, Lydia; Mtega, Wulystan Pius; Mwembe, Maria Nankya; Nkonyeni, Sixolile (University of Pretoria, 2016)
With the enhancement of information and communication technology, science and society has begun to accept that "indigenous knowledge and indigenous knowledge systems are blending with the modern scientific and technical knowledge" (Jain & Jibril, 2016:2). More and more, indigenous knowledge is becoming significant world-wide. The continued existence of every culture, depends on its folklores, legends, customs, rituals, beliefs the knowledge that supports this needs to be preserved for future generations. For this reason, the capturing and preservation of indigenous knowledge is definitely essential for the preservation of the local communities and their identity, which is strongly related to their culture and development of Africa as a whole.
Presentaion paper
Keywords: Council for Scientific and Industrial Research [CSIR], Communication Technology, Africa